2008
DOI: 10.1038/nature06858
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in human NPY expression affects stress response and emotion

Abstract: Understanding inter-individual differences in stress response requires the explanation of genetic influences at multiple phenotypic levels, including complex behaviours and the metabolic responses of brain regions to emotional stimuli. Neuropeptide Y (NPY) is anxiolytic 1,2 and its release is induced by stress 3 . NPY is abundantly expressed in regions of the limbic system that are implicated in arousal and in the assignment of emotional valences to stimuli and memories [4][5][6] . Here we show that haplotype-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
367
4
9

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 390 publications
(403 citation statements)
references
References 36 publications
19
367
4
9
Order By: Relevance
“…[48][49][50] Higher genotype-driven NPY expression has been recently shown to be associated with reduced pain/stress-induced activations of endogenous opioid neurotransmission and accounted for 37% variance in left posterior insular cortex activation. 44 Hence, our fMRI findings replicate previously reported NPY-related alterations in the processing of aversive stimuli while extending evidence for an interaction of NPY with reward circuits. Taken together, our findings provide evidence that increased NPY dosage is not only reflected by the peripheral biomarker of increased NPY plasma concentration but also by fMRI-elicited alteration in brain function related to reward and emotion processing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[48][49][50] Higher genotype-driven NPY expression has been recently shown to be associated with reduced pain/stress-induced activations of endogenous opioid neurotransmission and accounted for 37% variance in left posterior insular cortex activation. 44 Hence, our fMRI findings replicate previously reported NPY-related alterations in the processing of aversive stimuli while extending evidence for an interaction of NPY with reward circuits. Taken together, our findings provide evidence that increased NPY dosage is not only reflected by the peripheral biomarker of increased NPY plasma concentration but also by fMRI-elicited alteration in brain function related to reward and emotion processing.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, NPY participates in the regulation of feeding, circadian rhythms, reproduction and thermoregulation. 42,43 Although it has been widely investigated in the context of energy balance and body weight regulation, NPY has recently not only been implicated in behavioural traits, particularly negative emotionality and aggression, 44 but also in several neuropsychiatric disorders including depression, panic disorder, bipolar disorder and schizophrenia. 45 A functional polymorphism in the human NPY (Leu7Pro) resulting in increased NPY release from sympathetic nerves is associated with characteristics of metabolic syndrome and it has been suggested that the Pro7 allele is associated with an increased risk for alcohol dependence, a common comorbid disorder of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…One of the positive predictors of placebo effects, resilience, as defined by the ER-89 scale, refers to a person's ability to adapt successfully to acute stress, trauma or more chronic forms of adversity (Feder et al, 2009). This trait is thought to be mediated by positive emotions (Fredrickson et al, 2003) and adaptive changes in reward and emotional processing circuits (Feder et al, 2009), which may include interactions with the endogenous opioid system (Zhou et al, 2008). Animal models of stress resiliency have linked this trait to lower levels of ventral tegmental area dopamine neuron excitability (Krishnan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a link between haplotype-driven NPY expression and individual differences in stress response and emotion has been observed (6). Additionally, data from American soldiers undergoing survival training demonstrated that acute uncontrollable stress significantly increases plasma NPY concentrations.…”
mentioning
confidence: 99%